Análise da influência de diferentes meios de armazenagem na viabilidade de fibroblastos e na composição iônica da dentina radicular: estudo in vitro - Silva, Ivanilton Alan de Souza (2015)
For preservation of periodontal ligament cells after one tooth avulsion becomes necessary to determine a storage medium. The aim of this study was to analyze the preservation of human fibroblast cells and analyze the composition of root dentin of bovine teeth in different storage media. Immortalized human fibroblasts cells were grown in flasks containing Dulbecco's modified eagle medium (DMEM), and ffter reaching confluence the cells were trypsinized, counted by hemocytometer and plated. The culture medium was removed from each well and the cells were exposed at different times in the solutions: GLi - milk; GRl - ringer’s lactate; GPv - red propolis solution and GPd - Pedialyte. DMEM was considered positive control group and tap water was the negative control. After the experimental period of 15, 30, 45 and 60 minutes, we used the colorimetric method MTT formazan. For analysis of surface composition of root dentin, were using Fourier transform infrared (FTIR) where, were collected 60 bovine incisors. Samples were extracted from the cervical region of the root dentin in 3x3mm. The samples were randomly divided among experimental groups in differents times. Data were tabulated and statistically analyzed using analysis of variance for the storage media within each time and the time factor for each storage medium, followed by Dunnet test and Tukey's test (P <0.05 ). In 15 and 60 minutes, from the media types, the milk and Ringer's lactate showed better results when compared to the negative control. However, in 30 and 45 minutes only the milk showed satisfactory results. A comparison with DMEM only the milk showed similar statistical results. In assessing the viability of human fibroblasts, milk showed cell viability levels similar to the positive control and superior to other media tested. Within 60 minutes storage, the one most commonly used in clinical conditions, the ringer's lactate has higher performance than the red propolis and the pedialyte and these similar to tap water (negative control).